Validity of Research Based Book on Isolation, Amplification, and Visualization Material for Biotechnology Course in Higher Education - Rizka, Chairany; Harahap, Fauziyah; Edi, Syahmi (META: Journal of Science and Technological Education, 2022)
Biotechnology is a discipline of biology that examines the use of methods or how to utilize living things and its components in terms of increasing the welfare of human existence. Biotechnology courses currently require instructional materials, particularly those pertaining to the application of DNA isolation and amplification. The aim of this study was to determine the level of validity of research based book on isolation, amplification, and visualization material for biotechnology course in higher education. The  parameters  measured were the validity of the research based book from the aspect of material, language, context, and design. This study uses developmental stage that followed Borg and Gall (1989) development model. The results of the validation by experts were obtained using a questionnaire instrument. The research based book on isolation, amplification, and visualization topic passed validation by materials experts, linguists experts, and design experts with scores of 84% (very good), 77% (very good), and 85%. (very good). It can be concluded that research based book on isolation, amplification, and visualization material product is feasible to use for learning in biotechnology course in higher education based on its validity.